Insulating coating for energy storage cabinet and preparation method thereof
By using modified acrylic emulsion, the problem of energy storage cabinet insulating coatings is easily cracked in outdoor environments, and the effect of improving resistivity, weather resistance and extending service life is achieved.
Patent Information
- Application Number
- CN202411382234.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing insulating coatings used in energy storage cabinets are prone to cracking in outdoor environments and have a short service life.
Modified acrylic emulsion is used as the film forming substance. The modified acrylic emulsion is composed of unsaturated fluorosilicide, alkyl acrylate, and hydroxyacrylate monomers. It is modified by specific unsaturated fluorosilicide resin to form a three-dimensional network structure film structure to improve resistivity, weather resistance, low temperature resistance and corrosion resistance.
Effectively prevent insulating coatings from cracking in outdoor environments, improve the adhesion fastness with energy storage cabinets, extend service life, and maintain the advantages of stable and difficult to delaminate.
Smart Images

Figure BDA0005070182650000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and in particular to an insulating coating for energy storage cabinets and a preparation method thereof. Background Art
[0002] An energy storage cabinet is a device used to store electrical energy. It usually consists of a battery pack, a battery management system (BMS), an energy management system (EMS), power electronic converters (such as inverters and rectifiers), and related control and protection equipment.
[0003] The cabinet structure of the energy storage cabinet is usually made of metal. In order to prevent the cabinet structure from being easily corroded in outdoor environments, the relevant technology usually coats a layer of paint on the surface of the cabinet structure. The coating formed by the curing of the paint isolates the air, moisture and chemicals, and protects the cabinet structure from corrosion. However, it should be noted that the paint used for energy storage cabinets usually needs to have excellent insulation properties, otherwise a short circuit will occur between the electrical components in the energy storage cabinet and the metal casing, which will cause electrical safety accidents such as fire and electric shock.
[0004] At present, for environmental protection reasons, the insulating coatings commonly used in energy storage cabinets usually use water-based acrylic resins, water-based polyurethane resins or epoxy resins as film-forming materials, and then add insulating fillers, dispersants, wetting agents, leveling agents and other additives and mix them together. However, the above insulating coatings are prone to cracking in outdoor environments and have a short service life. Summary of the invention
[0005] In order to improve the problem in the related art that insulating coatings for energy storage cabinets are prone to cracking in outdoor environments, the present application provides an insulating coating for an energy storage cabinet and a preparation method thereof.
[0006] In the first aspect, the present application provides an insulating coating for an energy storage cabinet using the following technical solution:
[0007] An insulating coating for an energy storage cabinet comprises 100 parts by weight of a modified acrylic emulsion, 10-15 parts by weight of an insulating filler, 4-8 parts by weight of a silane coupling agent, 3-4 parts by weight of a wetting agent and 20-30 parts by weight of a dispersant. The modified acrylic emulsion is a copolymer emulsion of an unsaturated fluorosilicone resin, an alkyl acrylate and a hydroxy acrylate monomer. The unsaturated fluorosilicone resin is a reaction product of glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate.
[0008] The difference between the insulating coating of the present application and the existing coating is that the film-forming material of the insulating coating of the present application adopts modified acrylic emulsion, which is a copolymer emulsion of unsaturated fluorosilicone resin, alkyl acrylate, and hydroxy acrylate monomers, and the unsaturated fluorosilicone resin adopts the reaction product of glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate through the reaction of epoxy group and amino group. Among them, the present application modifies the acrylic emulsion by a specific unsaturated fluorosilicone resin, and a stable membrane structure with a three-dimensional network structure can be obtained, which is beneficial to improve the resistivity, weather resistance, low temperature resistance and corrosion resistance of the membrane structure, and can prevent the problem of easy cracking of the insulating coating in the outdoor environment. At the same time, the introduction of hydroxy acrylate monomers and wetting agents can improve the wettability of the insulating coating to metal materials, which is beneficial to improve the adhesion strength of the insulating coating to the energy storage cabinet, and can effectively extend the service life of the insulating coating.
[0009] In some specific embodiments, in the unsaturated fluorosilicone resin, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is (1.2-1.5):1.
[0010] In the unsaturated fluorosilicone resin of the present application, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is preferably (1.2-1.5):1, which can prevent the insulating coating from cracking in the outdoor environment while further improving the adhesion between the insulating coating and the energy storage cabinet.
[0011] In some specific embodiments, in the glycidyl ether propyl mono-terminated polydimethylsiloxane, the polymerization degree of the dimethylsiloxane segment is 20-30.
[0012] In the present application, in the glycidyl ether propyl mono-terminated polydimethylsiloxane, the degree of polymerization of the dimethylsiloxane segment is controlled within the range of 20-30, so that a stable insulating coating that is not easy to delaminate can be obtained while obtaining a membrane structure with excellent low-temperature resistance.
[0013] In some specific embodiments, the preparation method of the unsaturated fluorosilicone resin is as follows:
[0014] Glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate are added to the solvent, stirred for reaction for 1-1.5 hours, and then the solvent is removed by distillation under reduced pressure to obtain an unsaturated fluorosilicone resin.
[0015] In some specific embodiments, the raw materials for preparing the modified acrylic emulsion include unsaturated fluorosilicone resin, alkyl acrylate, hydroxy acrylate monomer, emulsifier, initiator and water, and the weight ratio of the unsaturated fluorosilicone resin, alkyl acrylate, hydroxy acrylate monomer, emulsifier, initiator and water is (20-25): (60-70): (10-15): (3-4): (1-2): 100.
[0016] Among the raw materials for preparing the modified acrylic emulsion of the present application, the weight ratio of unsaturated fluorosilicone resin, alkyl acrylate, hydroxy acrylate monomer, emulsifier, initiator and water is preferably (20-25): (60-70): (10-15): (3-4): (1-2): 100, which can obtain an insulating coating that is not easy to crack in an outdoor environment and has strong adhesion to the energy storage cabinet. At the same time, the insulating coating has the advantages of being stable and not easy to delaminate.
[0017] In some specific embodiments, the alkyl acrylate is at least one of methyl acrylate, ethyl acrylate, and butyl acrylate, and the hydroxy acrylate is at least one of hydroxyethyl acrylate and hydroxybutyl acrylate.
[0018] In some specific embodiments, the emulsifier is at least one of diglycerol monoisostearate, poly-3-glycerol monoisostearate, and alkylphenol polyoxyethylene ether, and the initiator is an aqueous solution of ammonium persulfate, sodium persulfate, or potassium persulfate with a mass concentration of 0.1-0.2%.
[0019] In the present application, the use of the above-mentioned emulsifier is conducive to the stable storage of the insulating coating, and the initiator is preferably an aqueous solution of ammonium persulfate, sodium persulfate or potassium persulfate with a mass concentration of 0.1-0.2%, which is conducive to improving the safety of the copolymerization reaction.
[0020] In some specific embodiments, the preparation method of the modified acrylic emulsion comprises the following steps:
[0021] The water is mixed with an emulsifier to obtain an emulsifier solution, and then unsaturated fluorosilicone resin, alkyl acrylate, and hydroxy acrylate monomers are added to the emulsifier solution. After stirring evenly, an initiator is added dropwise, and the temperature is controlled at 65-75° C. to react for 3-4 hours to obtain a modified acrylic emulsion.
[0022] In the present application, the modified acrylic emulsion is prepared by the above method, which can improve the easy cracking problem of the insulating coating film structure, and at the same time, has the advantages of simple steps and convenient operation.
[0023] In some specific embodiments, the insulating filler is at least one of nano-calcium carbonate, nano-silicon dioxide, nano-magnesium carbonate, and nano-glass beads.
[0024] In a second aspect, the present application provides a method for preparing an insulating coating for an energy storage cabinet, which adopts the following technical solution:
[0025] A method for preparing an insulating coating for an energy storage cabinet comprises the following steps:
[0026] Adding the insulating filler, silane coupling agent and wetting agent into the dispersant and stirring evenly to obtain an intermediate product;
[0027] Add modified acrylic emulsion to the intermediate product and stir evenly to obtain insulating coating.
[0028] In the present application, insulating filler, silane coupling agent and wetting agent are first added to the dispersant, stirred evenly, and then the modified acrylic emulsion is added, which is beneficial to promoting the uniform dispersion of the raw materials and obtaining an insulating coating that can be stably stored.
[0029] In summary, the technical solution of this application includes at least the following beneficial technical effects:
[0030] (1) The film-forming material of the insulating coating of the present application adopts a modified acrylic emulsion, which is a copolymer emulsion of unsaturated fluorosilicone resin, alkyl acrylate, and hydroxy acrylate monomers, and the unsaturated fluorosilicone resin adopts the reaction product of glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate through the reaction of epoxy group and amino group. Among them, the present application modifies the acrylic emulsion by a specific unsaturated fluorosilicone resin to obtain a membrane structure with a stable three-dimensional network structure, which is beneficial to improve the resistivity, weather resistance, low temperature resistance and corrosion resistance of the membrane structure, and can prevent the problem of easy cracking of the insulating coating in the outdoor environment. At the same time, the introduction of hydroxy acrylate monomers and wetting agents can improve the wettability of the insulating coating to metal materials, which is beneficial to improve the adhesion strength between the insulating coating and the energy storage cabinet, and can effectively extend the service life of the insulating coating.
[0031] (2) In the unsaturated fluorosilicone resin of the present application, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is preferably (1.2-1.5):1, which can prevent the insulating coating from cracking in the outdoor environment while further improving the adhesion between the insulating coating and the energy storage cabinet.
[0032] (3) Among the raw materials for preparing the modified acrylic emulsion of the present application, the weight ratio of unsaturated fluorosilicone resin, alkyl acrylate, hydroxy acrylate monomer, emulsifier, initiator and water is preferably (20-25): (60-70): (10-15): (3-4): (1-2): 100, which can obtain an insulating coating that is not easy to crack in outdoor environments and has strong adhesion to the energy storage cabinet. At the same time, the insulating coating has the advantages of being stable and not easy to delaminate. DETAILED DESCRIPTION
[0033] The following is a further explanation based on specific experiments.
[0034] Preparation Example
[0035] [Preparation Example 1]
[0036] A modified acrylic emulsion, the preparation raw materials include 20kg unsaturated fluorosilicone resin, 70kg ethyl acrylate, 10kg hydroxyethyl acrylate, 3kg OP-10, 1kg 0.1% ammonium persulfate aqueous solution and 100kg water. The unsaturated fluorosilicone resin is obtained by reacting glycidyl ether propyl mono-terminated polydimethylsiloxane with 4-amino-3-fluoroallyl benzoate in a molar ratio of 1:1, and the structural formula of glycidyl ether propyl mono-terminated polydimethylsiloxane is (CH 3 ) 3 SiO[Si(CH 3 ) 2 O] n Si(CH 3 ) 2 (CH 2 ) 3 0CH 2 CH(O)CH 2 , the degree of polymerization n of the dimethylsiloxane chain segment is 20.
[0037] In this preparation example, the preparation method of the modified acrylic emulsion comprises the following steps:
[0038] Glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate were added to dimethyl sulfoxide, stirred for reaction for 1 hour, and then dimethyl sulfoxide was removed by vacuum distillation to obtain an unsaturated fluorosilicone resin;
[0039] Mix water and OP-10 to obtain an emulsifier solution, then add unsaturated fluorosilicone resin, ethyl acrylate and hydroxyethyl acrylate to the emulsifier solution, stir evenly, dropwise add an aqueous solution of ammonium persulfate, control the temperature at 65°C to react for 4 hours, and obtain a modified acrylic emulsion.
[0040] [Preparation Example 2]
[0041] A modified acrylic emulsion, the preparation raw materials include 25kg unsaturated fluorosilicone resin, 60kg methyl acrylate, 15kg hydroxybutyl acrylate, 4kg OP-10, 2kg potassium persulfate aqueous solution with a mass concentration of 0.1% and 100kg water. The unsaturated fluorosilicone resin is obtained by reacting glycidyl ether propyl mono-terminated polydimethylsiloxane with 4-amino-3-fluoroallyl benzoate in a molar ratio of 1:1, and the structural formula of glycidyl ether propyl mono-terminated polydimethylsiloxane is (CH 3 ) 3 SiO[Si(CH 3 ) 2 O] n Si(CH 3 ) 2 (CH 2 ) 3 0CH 2 CH(O)CH 2 , the degree of polymerization n of the dimethylsiloxane chain segment is 20.
[0042] In this preparation example, the preparation method of the modified acrylic emulsion comprises the following steps:
[0043] Glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate were added to dimethyl sulfoxide, stirred for reaction for 1.5 hours, and then dimethyl sulfoxide was removed by vacuum distillation to obtain an unsaturated fluorosilicone resin;
[0044] Mix water and OP-10 to obtain an emulsifier solution, then add unsaturated fluorosilicone resin, methyl acrylate and hydroxybutyl acrylate to the emulsifier solution, stir evenly, dropwise add potassium persulfate aqueous solution, control the temperature at 75°C to react for 3 hours, and obtain a modified acrylic emulsion.
[0045] [Preparation Example 3]
[0046] A modified acrylic emulsion, which is different from [Preparation Example 1] in that: in the unsaturated fluorosilicone resin of this preparation example, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is 1.2:1.
[0047] [Preparation Example 4]
[0048] A modified acrylic emulsion, which is different from [Preparation Example 1] in that: in the unsaturated fluorosilicone resin of this preparation example, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is 1.5:1.
[0049] [Preparation Example 5]
[0050] A modified acrylic emulsion is different from [Preparation Example 1] in that: in the unsaturated fluorosilicone resin of this preparation example, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is 2:1.
[0051] [Preparation Example 6]
[0052] A modified acrylic emulsion, which differs from [Preparation Example 4] in that the degree of polymerization n of the dimethylsiloxane chain segment in the glycidyl ether propyl mono-terminated polydimethylsiloxane used in the unsaturated fluorosilicone resin of this preparation example is 25.
[0053] [Preparation Example 7]
[0054] A modified acrylic emulsion, which differs from [Preparation Example 4] in that the polymerization degree n of the dimethylsiloxane chain segment in the glycidyl ether propyl mono-terminated polydimethylsiloxane used in the unsaturated fluorosilicone resin of this preparation example is 30.
[0055] [Preparation Example 8]
[0056] A modified acrylic emulsion, which differs from [Preparation Example 4] in that the polymerization degree n of the dimethylsiloxane chain segment in the glycidyl ether propyl mono-terminated polydimethylsiloxane used in the unsaturated fluorosilicone resin of this preparation example is 40.
[0057] Example
[0058] [Example 1]
[0059] An insulating coating for an energy storage cabinet comprises 100 kg of modified acrylic emulsion prepared in [Preparation Example 1], 10 kg of nano calcium carbonate, 4 kg of silane coupling agent KH550, 4 kg of wetting agent (RK-8209 from Ruike Chemical) and 20 kg of water.
[0060] In this embodiment, a method for preparing an insulating coating for an energy storage cabinet comprises the following steps:
[0061] Add nano calcium carbonate, silane coupling agent KH550 and wetting agent into water and stir evenly to obtain an intermediate product;
[0062] Add modified acrylic emulsion to the intermediate product, stir evenly, and obtain insulating coating.
[0063] [Example 2]
[0064] An insulating coating for an energy storage cabinet comprises 100 kg of modified acrylic emulsion prepared in [Preparation Example 2], 15 kg of nano calcium carbonate, 8 kg of silane coupling agent KH550, 3 kg of wetting agent (RK-8209 from Ruike Chemical) and 30 kg of water.
[0065] In this embodiment, a method for preparing an insulating coating for an energy storage cabinet comprises the following steps:
[0066] Add nano calcium carbonate, silane coupling agent KH550 and wetting agent into water and stir evenly to obtain an intermediate product;
[0067] Add modified acrylic emulsion to the intermediate product, stir evenly, and obtain insulating coating.
[0068] [Example 3]
[0069] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion of this example adopts the modified acrylic emulsion prepared in [Preparation Example 3].
[0070] [Example 4]
[0071] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion of this example adopts the modified acrylic emulsion prepared in [Preparation Example 4].
[0072] [Example 5]
[0073] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion of this example adopts the modified acrylic emulsion prepared in [Preparation Example 5].
[0074] [Example 6]
[0075] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion of this example adopts the modified acrylic emulsion prepared in [Preparation Example 6].
[0076] [Example 7]
[0077] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion of this example adopts the modified acrylic emulsion prepared in [Preparation Example 7].
[0078] [Example 8]
[0079] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion of this example adopts the modified acrylic emulsion prepared in [Preparation Example 8].
[0080] Comparative Example
[0081] [Comparative Example 1]
[0082] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that the modified acrylic emulsion is different.
[0083] In this comparative example, the raw materials for preparing the modified acrylic emulsion include 10kg of vinyl-terminated hydroxyl-terminated polydimethylsiloxane, 5kg of styrene, 5kg of trifluoroethyl methacrylate, 70kg of ethyl acrylate, 10kg of hydroxyethyl acrylate, 3kg of OP-10, 1kg of 0.1% ammonium persulfate aqueous solution and 100kg of water. Among them, the polymerization degree of the dimethylsiloxane segment in the vinyl-terminated hydroxyl-terminated polydimethylsiloxane is 20.
[0084] In addition, the preparation method of the modified acrylic emulsion of this comparative example is as follows:
[0085] Mix water with OP-10 to obtain an emulsifier solution, then add vinyl-terminated hydroxyl-terminated polydimethylsiloxane, styrene, trifluoroethyl methacrylate, ethyl acrylate, and hydroxyethyl acrylate to the emulsifier solution, stir evenly, add dropwise an aqueous solution of ammonium persulfate, control the temperature at 65°C to react for 4 hours, and obtain a modified acrylic emulsion.
[0086] [Comparative Example 2]
[0087] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that 4-amino-3-fluoroallyl benzoate is replaced by an equimolar amount of p-vinylbenzylamine.
[0088] [Comparative Example 3]
[0089] An insulating coating for an energy storage cabinet, which differs from [Example 1] in that glycidyl ether propyl mono-terminated polydimethylsiloxane is replaced by an equal molar amount of 1,6-hexanediol glycidyl ether.
[0090] Performance testing
[0091] Preparation of the test sample: Using aluminum alloy as the substrate, the insulating coatings in each embodiment and comparative example were sprayed on the aluminum alloy substrate with a spraying thickness of 15 μm, and then placed in an environment of 150° C. for curing for 1 min, taken out, and left to stand for 48 hours to obtain the test sample.
[0092] Test 1: Adhesion grade: Referring to GB / T 9286-2021 "Scratch test method for paint and varnish", the adhesion grade of the test samples corresponding to each embodiment and comparative example was tested using adhesive tape. The adhesion grade is divided into 6 grades: 0, 1, 2, 3, 4, and 5. The lower the grade, the better the adhesion stability between the coating and the substrate.
[0093] Test 2: Corrosion resistance: Prepare a sulfuric acid solution with a mass concentration of 1% and a sodium hydroxide solution with a mass concentration of 1%, place the test samples corresponding to each embodiment and comparative example in a spray box, control the temperature in the spray box to 25°C, and the relative humidity to be greater than 95%. One group is continuously sprayed with sulfuric acid solution, and the other group is continuously sprayed with sodium hydroxide solution. The spraying time is 240h. After the spraying is completed, the sample is washed with water, and after natural drying, the sample is inspected for appearance and corrosion resistance rating. Among them, the coating color remains unchanged and the base metal is not corroded, which is the first level, the coating color becomes darker, and the local bulging is the second level, the coating corrosion area is 3-15% or the base metal has corrosion points, which is the third level, and the coating corrosion area is greater than 15% or the base metal has block corrosion, which is the fourth level.
[0094] Test 3: Weathering resistance: Referring to GB / T 1865-2009 "Artificial weathering and artificial radiation exposure of paints and varnishes to filtered xenon arc radiation", the test samples corresponding to each embodiment and comparative example were aged using method 1. The specific operation was as follows: the wavelength was controlled to be 360-400nm, and the aging was continued for 1000h to obtain an aged sample. Then, the aged sample was subjected to a corrosion test according to test 2, and the corrosion resistance grade of the aged sample was recorded.
[0095] Test 4: Low temperature resistance: The test samples corresponding to the embodiments and comparative examples were placed in an environment with a temperature of -15°C, left to stand for 48 hours, then removed and left at room temperature in a natural state to obtain the samples after low temperature treatment. Then, the aged samples were subjected to a corrosion test in accordance with Test 2, and the corrosion resistance level of the aged samples was recorded.
[0096] Test 5: Surface resistivity: Referring to QJ 2220.2-1992 "Test method for electrical insulation performance of coatings - Test method for insulation resistance, surface resistivity and volume resistivity", the surface resistivity of the coatings prepared from the insulating coatings in the embodiments and comparative examples was tested, wherein the higher the surface resistivity, the better the insulation properties of the coating.
[0097] Test 6: Insulation coating stability: The insulation coatings in the examples and comparative examples were tested for stability in accordance with 4.10 of GB / T 20623-2006, and whether stratification or floccules occurred was recorded in Table 1. Test conditions: rotation speed 5000 r / min, stirring for 0.5 h.
[0098] Table 1
[0099]
[0100] By comparing Example 1 with Comparative Example 1, it can be seen that the modified acrylic emulsion used in the insulating coating in Comparative Example 1 also contains fluorine groups, siloxane groups and phenyl groups, but the introduction method of Comparative Example 1 is different from that of Example 1. Example 1 of the present application introduces fluorine groups, siloxane groups and phenyl groups into the acrylic emulsion through the reaction product of glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate. Combined with the test data in Table 1, it can be seen that the corrosion resistance of the insulating coating in Example 1 after aging and low-temperature treatment is better than that of Comparative Example 1, and the mechanical stability of the insulating coating of Example 1 is better than that of the insulating coating of Comparative Example 1. It can be seen that the insulating coating of Example 1 of the present application has better weather resistance, low-temperature resistance and mechanical stability than the insulating coating in Comparative Example 1.
[0101] Comparing Example 1 with Comparative Example 2, it can be seen that the 4-amino-3-fluoroallyl benzoate used to prepare the unsaturated resin in Comparative Example 2 is replaced by an equimolar amount of p-vinylbenzylamine. Combined with the test data in Table 1, it can be seen that after 4-amino-3-fluoroallyl benzoate is replaced by an equimolar amount of p-vinylbenzylamine, the corrosion resistance of the insulating coating in Comparative Example 2 after aging is significantly reduced, indicating that the unsaturated fluorosilicone resin obtained by the reaction of 4-amino-3-fluoroallyl benzoate and glycidyl ether propyl mono-terminated polydimethylsiloxane is used to prepare the modified acrylic emulsion, which is more conducive to improving the weather resistance of the insulating coating.
[0102] Comparing Example 1 with Comparative Example 3, it can be seen that the glycidyl ether propyl mono-terminated polydimethylsiloxane used to prepare the unsaturated resin in Comparative Example 3 is replaced by an equal molar amount of 1,6-hexanediol glycidyl ether. Combined with the test data in Table 1, it can be seen that after the glycidyl ether propyl mono-terminated polydimethylsiloxane is replaced by an equal molar amount of 1,6-hexanediol glycidyl ether, the corrosion resistance, corrosion resistance after aging, and corrosion resistance after low-temperature treatment of the insulating coating in Comparative Example 3 are significantly reduced, indicating that the unsaturated fluorosilicone resin obtained by the reaction of 4-amino-3-fluoroallyl benzoate and glycidyl ether propyl mono-terminated polydimethylsiloxane is used to prepare the modified acrylic emulsion, which is more conducive to improving the corrosion resistance, weather resistance and low-temperature resistance of the insulating coating.
[0103] By comparing Example 1 with Examples 3-5, it can be seen that the difference between Example 1 and Examples 3-5 is that the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is different. Combining the test data in Table 1, it can be seen that when the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is within the range of (1.2-1.5):1, the adhesion fastness of the insulating coating to the substrate can reach level 0.
[0104] By comparing Example 4 with Examples 6-8, it can be seen that the difference between Example 4 and Examples 6-8 is that the polymerization degree of the dimethylsiloxane segment in the glycidyl ether propyl mono-terminated polydimethylsiloxane is different. Among them, the polymerization degree of the dimethylsiloxane segment is controlled within the range of 20-30, which is conducive to obtaining an insulating coating with good mechanical stability and not prone to delamination.
[0105] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An insulating coating, characterized in that: The invention comprises 100 parts by weight of a modified acrylic emulsion, 10-15 parts by weight of an insulating filler, 4-8 parts by weight of a silane coupling agent, 3-4 parts by weight of a wetting agent and 20-30 parts by weight of a dispersant. The raw materials for preparing the modified acrylic emulsion comprise an unsaturated fluorosilicone resin, an alkyl acrylate, a hydroxy acrylate monomer, an emulsifier, an initiator and water. The weight ratio of the unsaturated fluorosilicone resin, the alkyl acrylate, the hydroxy acrylate monomer, the emulsifier, the initiator and the water is (20-25): (60-70): (10-15): (3-4): (1-2):
100. The unsaturated fluorosilicone resin is a reaction product of glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate. The preparation method of the unsaturated fluorosilicone resin is as follows: Glycidyl ether propyl mono-terminated polydimethylsiloxane and 4-amino-3-fluoroallyl benzoate are added to the solvent, stirred for reaction for 1-1.5 hours, and then the solvent is removed by distillation under reduced pressure to obtain an unsaturated fluorosilicone resin; Wherein, the molar ratio of glycidyl ether propyl mono-terminated polydimethylsiloxane to 4-amino-3-fluoroallyl benzoate is (1.2-1.5):
1.
2. The insulating coating according to claim 1, characterized in that: In the glycidyl ether propyl mono-terminated polydimethylsiloxane, the polymerization degree of the dimethylsiloxane chain segment is 20-30.
3. The insulating coating according to claim 1, characterized in that: The alkyl acrylate is at least one of methyl acrylate, ethyl acrylate and butyl acrylate, and the hydroxy acrylate is at least one of hydroxyethyl acrylate and hydroxybutyl acrylate.
4. The insulating coating according to claim 1, characterized in that: The emulsifier is at least one of diglycerol monoisostearate, poly-3-glycerol monoisostearate, and alkylphenol polyoxyethylene ether, and the initiator is an ammonium persulfate aqueous solution, a sodium persulfate aqueous solution, or a potassium persulfate aqueous solution with a mass concentration of 0.1-0.2%.
5. The insulating coating according to claim 1, characterized in that: The preparation method of the modified acrylic emulsion comprises the following steps: The water is mixed with an emulsifier to obtain an emulsifier solution, and then unsaturated fluorosilicone resin, alkyl acrylate, and hydroxy acrylate monomers are added to the emulsifier solution. After stirring evenly, an initiator is added dropwise, and the temperature is controlled at 65-75° C. to react for 3-4 hours to obtain a modified acrylic emulsion.
6. The insulating coating according to claim 1, characterized in that: The insulating filler is at least one of nano calcium carbonate, nano silicon dioxide, nano magnesium carbonate and nano glass micro beads.
7. A method for preparing an insulating coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: Adding the insulating filler, silane coupling agent and wetting agent into the dispersant and stirring evenly to obtain an intermediate product; Add modified acrylic emulsion to the intermediate product and stir evenly to obtain insulating coating.
Citation Information
Patent Citations
Waterproof coating and preparation method thereof
CN117384526A
Fluorosilicone modified acrylate resin, stain-resistant coating and preparation method of fluorosilicone modified acrylate resin and stain-resistant coating
CN117534797A